Makna dan Nilai Tuturan Ritual Lewak Tapo pada Kelompok Etnik Lamaholot di Pulau Adonara, Kabupaten Flores Timur - Simon Sabon Ola (Humaniora, 2009)
Lewak topo ceremony is a traditional ritual of Lamaholot an ethnic group in Adonara Island, East Florest regency. This ritual is performed in sacred ambience, either in its speech or supporting objects. This ritual is headed by molan 'traditional shaman' that is believed have pure personality. Ritual lewak topo consists of some steps. Each of them is espoused by ritual speech which contains symbolyc meaning. Symbolic meaning means the world view of Lamaholot people. Behind the meaning, it implies cultural values taken to be a way of behaving that is oriented in making harmonious relation in social and religious dimension.